2020
DOI: 10.3390/nu12071902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Cocoa Supplementation on Postprandial Apolipoproteins, Lipoprotein Subclasses, and Inflammatory Biomarkers in Adults with Type 2 Diabetes after a High-Fat Meal

Abstract: Dyslipidemia and inflammation exacerbate postprandial metabolic stress in people with diabetes. Acute dietary supplementation with polyphenols shows promise in improving postprandial metabolic stress in type 2 diabetes (T2D). Cocoa is a rich source of dietary polyphenols with demonstrated cardioprotective effects in adults without diabetes. To date, the acute effects of cocoa on postprandial lipids and inflammation have received little attention in the presence of T2D. This report expands on our earlier observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…For instance, consumption of HF foods accompanied by a fruit juice resulted in a significant decrease in plasma cholesterol and triglyceride concentration in healthy overweight subjects with a concomitant reduction of inflammatory response mediated by IL-6 and TNF-α [54]. On the other hand, Davis et al reported that an intake of polyphenol-rich cocoa could not improve postprandial inflammatory biomarkers (IL-6 and IL-1β) in subjects following HF meal intake [55]. According to Edirisinghe et al, serum concentration of IL-1β was not altered in individuals that consumed strawberry beverages alongside an HF meal [17].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, consumption of HF foods accompanied by a fruit juice resulted in a significant decrease in plasma cholesterol and triglyceride concentration in healthy overweight subjects with a concomitant reduction of inflammatory response mediated by IL-6 and TNF-α [54]. On the other hand, Davis et al reported that an intake of polyphenol-rich cocoa could not improve postprandial inflammatory biomarkers (IL-6 and IL-1β) in subjects following HF meal intake [55]. According to Edirisinghe et al, serum concentration of IL-1β was not altered in individuals that consumed strawberry beverages alongside an HF meal [17].…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to patients with metabolic syndrome (MetS), including patients with T2DM. The most commonly evaluated markers of inflammation, in this case, were C-reactive protein (CRP), ferritin in plasma, oxygen consumption and chemiluminescence in neutrophils, proinflammatory interleukins (IL1β, IL6, IL18), serum total antioxidant capacity (TAC), tumour necrosis factor alpha (TNFα)-alpha, 8-hydroxy-2′-deoxyguanosine (8-OHdG) and nitrite [ 49 , 59 , 60 , 61 , 62 , 63 , 64 ]. In our study, we used commonly known markers from blood counts, such as lymphocytes, neutrophils, platelets, as well as the calculated parameters: PLR, NLR and MPVLR, to assess the immune status.…”
Section: Discussionmentioning
confidence: 99%
“…These results disagree with data from in vitro studies [ 21 ] and some, but not all, cross-sectional studies [ 23 , 39 ]. On the other hand, intervention studies in humans have shown conflicting results likely due to the type and source of polyphenols used in the different interventions [ 40 , 41 , 42 ]. Indeed, the chemical structure of polyphenols and their disposition in the food matrices, as well as the combined consumption with other foods, affect the pharmacokinetic parameters of the molecules and the antioxidant and ant inflammatory effects in the postprandial phase and in the long term [ 43 ].…”
Section: Discussionmentioning
confidence: 99%